2015
DOI: 10.1002/chem.201502132
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Structural Reassignment of Lyngbyaloside C Highlighted by Intermolecular Ketene Esterification

Abstract: Lyngbyaloside C, a classic macrolide, isolated from Lyngbya bouilloni, has shown moderate anticancer activity against several cancer cell lines. Here, we report the first total synthesis and stereochemical configuration reassignment of lyngbyaloside C. The synthesis highlights a one-pot intermolecular ketene esterification reaction to form the crucial tertiary ester and tetrahydropyran. In addition, a novel and concise synthetic pathway towards the 1,3-syn secondary, tertiary diol fragment is described using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…The correct structure 86 of (−)‐lyngbyaloside B was finally verified in an unambiguous manner through total synthesis. In line with our conclusion, Taylor and co‐workers very recently reported the total synthesis of (−)‐18 Z ‐lyngbyaloside C and revised the original stereochemical assignment of the proposed structure 4 at the same positions as 1 (C‐10, C‐11, and C‐13) . Therefore, we suggest that the originally assigned structure 2 of lyngbouilloside should also be reconsidered carefully.…”
Section: Resultssupporting
confidence: 87%
“…The correct structure 86 of (−)‐lyngbyaloside B was finally verified in an unambiguous manner through total synthesis. In line with our conclusion, Taylor and co‐workers very recently reported the total synthesis of (−)‐18 Z ‐lyngbyaloside C and revised the original stereochemical assignment of the proposed structure 4 at the same positions as 1 (C‐10, C‐11, and C‐13) . Therefore, we suggest that the originally assigned structure 2 of lyngbouilloside should also be reconsidered carefully.…”
Section: Resultssupporting
confidence: 87%
“…Compounds 2-5 were identified by comparison of HRESIMS, 1 H NMR, and COSY spectral data to the literature [17][18][19][20] (data provided in supplementary material). Total syntheses have been reported for 2-4, confirming the structures of 2 [22] and 3 [23] while leading to the structural revision of three stereogenic centers (C-10, 11, and 13) of 4 [24]. Two natural products that appeared to belong to the lyngbyabellin class of natural products, referred to as lyngbyabellin-like 1 (LYN1) and 2 (LYN2), were isolated in very low yields (2.2 and 2.8 µg, respectively) which hindered full structure elucidation.…”
Section: Molecular Structures Of Natural Products From Moorea Producenssupporting
confidence: 52%
“…Total syntheses of the proposed 456 and correct structures (709) of (À)-lyngbyaloside B were completed 457 and total synthesis of the (18Z) and (18E) isomers of lyngbyaloside C 458 resulted in reassignment of the structures to 710 and 711 respectively. 459 As a result, it was suggested that the structure of lyngbouilloside 460 should likely also be reconsidered. 459 Total syntheses of the acyclic depsipeptide maedamide 461 and cyclodepsipeptide largamide B 462 also resulted in stereochemical revision of their structures to 712 (ref.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…459 As a result, it was suggested that the structure of lyngbouilloside 460 should likely also be reconsidered. 459 Total syntheses of the acyclic depsipeptide maedamide 461 and cyclodepsipeptide largamide B 462 also resulted in stereochemical revision of their structures to 712 (ref. 463) and 713 (ref.…”
Section: Cyanobacteriamentioning
confidence: 99%